2018
DOI: 10.1016/j.ibmb.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of corpora allata-corpora cardiaca microRNA repertoires revealed significant changes during mosquito metamorphosis

Abstract: The corpora allata (CA) are a pair of endocrine glands with neural connections to the brain and close association with another neuroendocrine organ, the corpora cardiaca (CC). The CA from adult female Aedes aegypti mosquitoes synthesize fluctuating levels of juvenile hormone (JH), which have been linked to the ovarian development and are influenced by nutritional signals. In this study, we investigated the potential involvement of microRNAs (miRNAs), a type of small non-coding RNAs, in the regulation of gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…In many insects, miRNAs have also been found to potentially regulate different sesquiterpenoid pathway genes ( Table 2 ). For instances, in mosquito A. aegypti , four JH biosynthetic enzyme genes including 3-hydroxy-3-methylglutaryl-coenzyme A reductase ( HMGR ), diphosphomevalonate decarboxylase ( PP-MevD ), aldehyde dehydrogenase ( ALDH ), and farnesyl-pyrophosphate synthase ( FPPS ) were in silico predicted to be potentially regulated by miRNAs ( Nouzova et al, 2018 ). In addition, in the adult female mosquito, mosquito specific miR-1890 targets JH-controlled chymotrypsin-like SP, JHA15 that involve in the regulation of blood digestion, ovary development and egg deposition ( Lucas et al, 2015 ).…”
Section: Microrna Regulations On Sesquiterpenoidsmentioning
confidence: 99%
“…In many insects, miRNAs have also been found to potentially regulate different sesquiterpenoid pathway genes ( Table 2 ). For instances, in mosquito A. aegypti , four JH biosynthetic enzyme genes including 3-hydroxy-3-methylglutaryl-coenzyme A reductase ( HMGR ), diphosphomevalonate decarboxylase ( PP-MevD ), aldehyde dehydrogenase ( ALDH ), and farnesyl-pyrophosphate synthase ( FPPS ) were in silico predicted to be potentially regulated by miRNAs ( Nouzova et al, 2018 ). In addition, in the adult female mosquito, mosquito specific miR-1890 targets JH-controlled chymotrypsin-like SP, JHA15 that involve in the regulation of blood digestion, ovary development and egg deposition ( Lucas et al, 2015 ).…”
Section: Microrna Regulations On Sesquiterpenoidsmentioning
confidence: 99%
“…RT-qPCR was performed on a BIO-RAD CFX Connect Real-Time System using a miRNA RT-qPCR assay kit (Tiangen, Beijing, China). The mature miR-3024 gene sequence was used as the forward primer and the U6 snRNA was used as a reference [41] (Table S1). The reactions were performed in a 20 µL volume of a mixture containing 1 µL 2×miRNA RT-qPCR mix, 1 µL cDNA template, 0.4 µL of each primer, and 8.2 µL of nuclease-free water.…”
Section: Rt-qpcr For Mirnamentioning
confidence: 99%
“…In contrast, in insects, it started with the pioneering work of Kopec (1922) about a century ago, with his discovery that the insect brain is an endocrine gland. Later, key pioneers were sir Vincent Wigglesworth with his discovery of JH synthesized by the CA, and Carroll M. Williams with the serendipitous discovery that the abdomen of male Hyalophora cecropia moths was a repository of high amounts of JH (references in Riddiford, 1994;Watt and Davey, 1996;Nijhout, 1998). It took many years before it became clear that the CA were not the only site of synthesis of farnesol/JHs.…”
Section: A Still Continuing Search: How Many Sites Of Farnesol/farnesmentioning
confidence: 99%
“…Later research showed that it is a much more complex issue and that sNPF plays, among other functions, a prominent role in the control of feeding (Carlson et al, 2013;Fadda et al, 2019). In addition, changes in microRNAs may also play a role (Nouzova et al, 2018a).…”
Section: Gland Cells Of the Corpora Allata Have Golgi Systems: A Probmentioning
confidence: 99%